Некоторые аспекты совершенствования процесса функционирования комплекса машин «харвестер + форвардер» - Izotova E. N. (Science and education: future development, 2017)
some directions of the solution of the task of perfection of the process of functioning of a complex of machines "harvester + forwarder" are shown. The work of Russian scientists in this direction is considered.
Keywords: технология; совершенствование; форвардер; improvement; technology; forwarder; харвестер; harvester